2021
DOI: 10.20473/vol8iss20214pp401-412
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Halal Destination Attributes Di Sumatera Barat Terhadap Wisatawan Muslim

Abstract: ABSTRAKSumatera Barat telah dinobatkan sebagai destinasi wisata halal terbaik di dunia karena memiliki halal destination attributes yang sangat ramah terhadap wisatawan Muslim. Dalam penelitian ini akan dijelaskan bagaimana pengaruh halal destination attributes di Sumatera Barat terhadap experience quality dan destination satisfaction dari wisatawan Muslim. Penelitian ini menggunakan pendekatan kuantitatif yang diuji dengan teknik analisis jalur dan diolah menggunakan program AMOS. Hasil penelitian menemukan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…From an Islamic perspective, the availability of HDAs might be used to satisfy Muslim tourists at a destination [3,60,61]. Noviyani and Ratnasari [62] also showed that HDAs have a significant positive effect on destination satisfaction. Furthermore, destination satisfaction might be achieved by the availability of Islamic attributes at a destination [52].…”
Section: Hdas and Destination Satisfactionmentioning
confidence: 99%
“…From an Islamic perspective, the availability of HDAs might be used to satisfy Muslim tourists at a destination [3,60,61]. Noviyani and Ratnasari [62] also showed that HDAs have a significant positive effect on destination satisfaction. Furthermore, destination satisfaction might be achieved by the availability of Islamic attributes at a destination [52].…”
Section: Hdas and Destination Satisfactionmentioning
confidence: 99%